If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5m+3=23.m=
We move all terms to the left:
5m+3-(23.m)=0
We add all the numbers together, and all the variables
5m-(+23.m)+3=0
We get rid of parentheses
5m-23.m+3=0
We add all the numbers together, and all the variables
-18m+3=0
We move all terms containing m to the left, all other terms to the right
-18m=-3
m=-3/-18
m=1/6
| 7(3w+6)^5=-7 | | 7(3w+6)^5=-7 | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6y+8=5y+10 | | 6y+8=5y+10 | | 6y+8=5y+10 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | x4+-3x2-10=0 | | y-11=3y-11 | | w/0.197=7.8 | | 5x10=-44-4x | | –k=–217 | | 7e+3.3=0.3 | | 3-6y=144 | | -6x^2-16x-8=0 | | –12=3(d+9) | | –12=3(d+9) | | –12=3(d+9) | | 1/3x−9=15 | | 6x+13=36 |